Factors that influence consumer buying behavior towards imported chocolates / Azyana Izzah Arshad and Nurul Anis Asheila Noor Azmi - Arshad, Azyana Izzah; Noor Azmi, Nurul Anis Asheila (Faculty of Business and Management, 2013)
This study aims to identify factors that influence consumer buying behavior towards imported chocolate namely quality, brand, social influence, and social status. It is also done to test which factors influence the most on the consumer behavior and then the results are used to generate suggestions to apply for local chocolate. A questionnaire was developed and distributed to 300 students of UiTM Melaka City Campus using convenience sampling method. Data was analyzed by using factor analysis in SPSS. The result shows that three (3) of the independent variables, that is quality, brand, and social status was founded to have significant towards the dependent variable. However, all independent variables have positive relationship with the dependent variable. And to the question of which of the independent variables are the most influence the dependent variable, the answer is brand.